Perancangan Aplikasi Edukasi Pembelajaran Tata Surya Pada Sekolah Dasar Menggunakan Metode ADDIE - Iren Anggi Stevani Silaen (CV. Graha Mitra Edukasi, 2025)
Learning is a process of interaction between students and educators and learning resources in a learning environment that includes teachers and students who exchange information. Learning is also a process to help students learn well. In the context of education, teachers teach a lesson so that students can learn and master the contents of the lesson to achieve a specified objective, can also influence changes in attitudes, and skills of a student, but this teaching process gives the impression of only one party's work, namely the teacher's work. ADDIE is an everyday term used to describe a systematic approach to learning development. In addition to the CBI, CAI, and other learning methods, the ADDIE method is also a method that is suitable for use in a learning system that will make it easier for teachers to deliver material. One way of computer-assisted learning is the application of the ADDIE method. The ADDIE method is one of the learning system design models that shows the basic stages of a simple and easy-to-learn learning system. In the computer-assisted learning process, where computers are used for the purpose of presenting learning in the form of tutorials, simulations, and games. This can really help students to be able to apply a learning system while playing which is very effective for the learning process for students.